Primary School Studentsâ€™ Analogical Reasoning in Solving Open-ended Word Problems - Egitayanti Aulia Rochman; Mohammad Faizal Amir (Al Ibtida: Jurnal Pendidikan Guru MI, 2023)
AbstractThis study aims to identify primary school students' analogical reasoning in solving open-ended word problems. This is qualitative research with a case study approach. The participants in this study were 25 fifth-grade primary school students selected using the purposive sampling technique to represent each category of analogical reasoning based on analogical reasoning tasks. Research instruments comprised of tests in analogical reasoning tasks and interview guidelines. Data analysis techniques included data reduction, presentation, and verification. Research results showed that there were three categories of students' analogical reasoning in solving word problems with close-ended source problems and open-ended target problems: (1) open comprehensive analogy, where students successfully solved the close-ended source problem and the open-ended target problem; (2) semi-open comprehensive analogy, where students successfully solved the close-ended source problem but did not successfully solve the open-ended target problem; and (3) failure in close-open analogy, where students did not successfully solve the close-ended source problem and the open-ended target problem. The results of this study suggest that educators, especially at the primary level, deepen students' ability to solve close-ended problems first so that students can solve open-ended problems with analogical reasoning.Keywords: analogical reasoning, problem-solving, open-ended, primary school.Â AbstrakPenelitian ini bertujuan untuk mengidentifikasi penalaran analogi siswa sekolah dasar dalam memecahkan word problems berbasis open-ended. Jenis penelitian yang digunakan adalah kualitatif dengan pendekatan studi kasus. Partisipan dalam penelitian ini sebanyak 25 siswa kelas lima sekolah dasar, untuk memilih subjek penelitian menggunakan teknik purposif yang mewakili setiap kategori penalaran analogi berdasarkan tugas penalaran analogi. Instrumen penelitian meliputi tes berupa analogical reasoning tasks dan pedoman wawancara. Teknik analisis data terdiri dari reduksi data, penyajian data, dan verifikasi data. Hasil penelitian menunjukkan bahwa terdapat tiga kategori penalaran analogi siswa ketika memecahkan word problems dengan masalah sumber close-ended dan masalah target open-ended, yaitu: (1) Analogi open comprehensive, siswa berhasil memecahkan masalah sumber close-ended dan masalah target open-ended; (2) Analogi semi-open comprehensive, siswa berhasil memecahkan masalah sumber close-ended tetapi tidak berhasil memecahkan masalah target yang open-ended; (3) Kegagalan analogi close-open, siswa tidak berhasil memecahkan masalah sumber close-ended dan masalah target open-ended. Hasil penelitian ini menyarankan kepada para pendidik khususnya di tingkat dasar untuk memperdalam kemampuan siswa dalam memecahkan masalah close-ended terlebih dahulu agar siswa bisa memecahkan masalah open-ended dengan penalaran analogi.Kata kunci: penalaran analogi, pemecahan masalah, open-ended, sekolah dasar.